Embedded Control and Remote Monitoring for Photovoltaic Solar Energy Harvesting Systems: A Review - Wei Chang C.C.; Ding T.J.; Tak Y.C.; Siaw Paw J.K.; Phing C.C. (Institute of Physics, 2023)
Control systems; Economic and social effects; Embedded systems; Energy harvesting; Fossil fuels; Monitoring; Solar energy conversion; Solar power generation; Control monitoring; Embedded control; Embedded monitoring and control; Energy harvesting systems; Monitoring and control; Monitoring and control systems; Photovoltaic solar energy; Photovoltaics; Remote monitoring; Solar energy harvesting; Solar energy